2011
DOI: 10.1007/978-3-642-19571-6_11
|View full text |Cite
|
Sign up to set email alerts
|

Unconditional and Composable Security Using a Single Stateful Tamper-Proof Hardware Token

Abstract: Abstract. Cryptographic assumptions regarding tamper proof hardware tokens have gained increasing attention. Even if the tamperproof hardware is issued by one of the parties, and hence not necessarily trusted by the other, many tasks become possible: Tamper proof hardware is sufficient for universally composable protocols, for informationtheoretically secure protocols, and even allow to create software which can only be used once (One-Time-Programs). However, all known protocols employing tamper-proof hardware… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 23 publications
1
56
1
Order By: Relevance
“…A consequence of this model is that the security of a player now depends only on its own token being good and holds even if tokens used by other players are not genuine! This new setup assumptions has gained a lot of interest and several works after [27] have shown that unconditional UC-security is possible [32,25], even using a single stateful token [22,23]. Note that a stateful token, in contrast with a stateless token, requires an updatable memory that can be subject to reset attacks.…”
mentioning
confidence: 99%
“…A consequence of this model is that the security of a player now depends only on its own token being good and holds even if tokens used by other players are not genuine! This new setup assumptions has gained a lot of interest and several works after [27] have shown that unconditional UC-security is possible [32,25], even using a single stateful token [22,23]. Note that a stateful token, in contrast with a stateless token, requires an updatable memory that can be subject to reset attacks.…”
mentioning
confidence: 99%
“…Our protocols are thus optimal in this regard. Note that a single stateful token suffices for universally composable OT [20]; our result thus demonstrates a separation between stateful and stateless tokens.…”
Section: Introductionmentioning
confidence: 54%
“…Goyal et al [29] show an unconditional construction of oblivious transfer (and hence general secure computation) using Θ(λ) stateful tokens. Döttling et al [20] show how to construct unconditionally secure OT using only a single stateful token. Goyal et al [28] showed that unconditional security from stateless tokens is impossible unless the token model is extended to allow Table 1: Universally composable OT based on stateless tamper-proof hardware tokens.…”
Section: Prior Workmentioning
confidence: 99%
See 2 more Smart Citations